Matters of fact and politics: Generating expectations of cancer screening. (July 2019) - Pienaar, Kiran; Petersen, Alan; Bowman, Diana M.
Abstract: Many countries, including Australia, the United Kingdom and the United States have established national screening programs in the effort to advance the early diagnosis of cancers. Australia has population screening programs for breast, bowel and cervical cancers, and this article focuses on breast and cervical cancer screening as the two longest running programs in Australia. While these screening programs are well-established and report relatively high participation rates, the effectiveness of population screening is a contested issue, subject to significant, ongoing debate about its purported benefits (Armstrong, 2019). In this article, we draw on ideas from sociology of science on the construction of scientific facts to analyse how evidentiary claims are presented in policy documents for Australia's breast and cervical cancer screening programs, and the implications for those who are the targets of screening. We explore how screening-related information assumes the status of scientific 'facts', and argue that presenting information as neutral and objective obscures the political choices involved in its generation. Importantly, some of the claims presented in the policy documents have a tendency to emphasise the benefits, and minimise the risks and harms of population-based screening. In doing so, we suggest that the current national policies may be contributing to sustaining expectations of screening that are higher than warranted. Higher expectations may bring with them unintended societal and economic costs to the public. We conclude by noting how deeply ingrained socio-cultural meanings of cancer shape public expectations of the protective value of screening, which allows current screening approaches to become further entrenched and resistant to challenge. Highlights: National cancer screening programs are justified on the basis of selective evidence. Screening policy emphasises the benefits of interventions and downplays the risks. Minimising the risks of screening sustains higher expectations than are warranted. Screening is entrenched due to a risk management ethos and the fear of cancer. Screening policy needs to better address the fragile balance of benefits and risks.